HEART AND DISEASES (International journal of artificial intelligence, 2025)
The heart is a vital organ responsible for pumping blood throughout the human body, supplying oxygen and nutrients to all tissues. Heart diseases are among the leading causes of death worldwide and include conditions such as coronary artery disease, heart failure, arrhythmia, and congenital heart defects. These disorders can result from unhealthy lifestyles, poor diet, lack of physical activity, smoking, and stress. Early diagnosis, proper treatment, and preventive measures such as regular exercise, balanced nutrition, and avoidance of harmful habits can significantly reduce the risk of heart diseases. This article discusses the structure and function of the heart, common types of heart diseases, their causes, prevention, and treatment methods.